Neuroblastoma: The basis for cure in limited‐resource settings. Issue 7 (2nd February 2021) - van Heerden, Jaques; Kruger, Mariana; Esterhuizen, Tonya Marianne; Pinxten, Wim
Abstract: Background: Neuroblastoma (NB) contributes the most to the mortality of childhood malignancies worldwide. The disease spectrum is heterogenous and the management complex and costly, especially in advanced disease or disease with adverse biology. In low‐ and middle‐income countries (LMICs) the majority of NB presents in advanced stages. Therefore, with limited resources and poor prognosis the treatment of NB is often not a priority. The aim of the study was to evaluate the research activities and perceptions of the management of NB that determine the research and treatment approaches in LMICs. Methods: Data were sourced from https://www.clinicaltrials.gov/ identifying NB trials open to LMIC. Abstracts on NB research presented at the International Society for Paediatric Oncology (SIOP) Congresses between 2014 and 2020 were evaluated according to income status. An online survey evaluating medical views on NB in LMICs and the effect on the management was conducted. Descriptive analysis was done. Where appropriate categorical association between covariates was assessed using the Pearson chi‐square (χ 2 ) test or Fishers exact test. Results: There were 15/562 (2.7%) trials open to LMIC. Only six of 138 (4.3%) LMIC participated in NB trials. Of the 688 abstracts presented between 2014 and 2020 at the SIOP International Congress on NB as primary subject, 297 (42.7%) were from LMICs. Only two were from low‐income countries (LICs). Sixty‐one countries responded to the NB survey. Positive views towards NB management were present when treatment was based on a national protocol, the availability of trimodal or advanced treatment options were present, and when a balance of metastatic or local disease were treated. Conclusion: Management of NB in LMICs should include increased advocacy and research as well as implementation of national management strategies.